Menganalisis Afiksasi Pada Dongeng "Beruang Mendidik Anaknya" Karya Puput Mugiati - Marina Dini Ari Pratiwi; Nuvitaliya Rahmawati; Dominggas Galanggoga; Sahrul Farosy; Firman Mauludin (Educational Journal, 2026)
This study aims to analyze the use of affixation in the animal fable entitled "Beruang Mendidik Anaknya" by Puput Mugiati. This fable tells the process of independence of a bear cub named Pony who learns to survive after being separated from his mother. The method used in this study is a qualitative descriptive method with reading, note-taking techniques in data collection, and content analysis, namely identifying affixed words found in the fable text. The results of the analysis show that the affixations found include prefixes, suffixes, and confixes. The prefixes that are predominantly used include me-, di-, ber-, ter-, ke-, and se-, such as in the words jump, left, and run. The suffixes found include -an and -nya, such as in the words visit and mother. In addition, there is also a confix ke-…-an as in the words departure and visible. The use of affixation in this fable serves to clarify the meaning of words, form variations in word classes, and enrich the sentence structure in the story. The research results show that there are 16 prefixes, 8 suffixes, and 3 confixes. The findings of affixation in the animal fable "The Bear Educates His Cub" are predominantly prefixed. Thus, it can be concluded that affixation plays a crucial role in building the integrity of meaning and the beauty of language in this animal fable.